OP0127 Ten years follow-up of gastrointestinal involvement by the small intestinal clearance in patients with systemic sclerosis. (15th June 2017) - Hashimoto, N; Kitano, M; Nakazawa, T; Iwasaki, T; Hashimoto, T
Abstract : Background: Systemic sclerosis (SSc) is an inflammatory autoimmune disease characterized by fibrosis and small vascular involvement in the skin, lungs, heart and gastrointestinal (GI) tract. The esophagus is the most frequently involved GI tract disorder. Although the small intestinal involvement such as malabsorption and pseudo-obstruction is less common, it has been related to morbidity and mortality of SSc patients. We previously reported a close correlation between the esophageal diameter and the small intestinal clearance (SIC) (EULAR 2011). We also suggested that anti-centromere antibodies (ACA) are an important factor of esophageal dilatation in SSc patients (EULAR 2010). However, changes of small intestinal involvement during long-term follow-up have not yet been defined. Objectives: The aim of this study was to evaluate a correlation between the small intestinal involvement and clinical features in SSc patients during ten years follow-up. Methods: Fifty-five patients with a definite diagnosis of SSc [52 female and 3male with mean age of 59.4 years (range 29–77 years)] were included in the study. Thirteen (23.6%) patients were classified as diffuse SSc and 42 (76.4%) as limited SSc. The SIC grade was classified according to barium meal reach at 30 min after intake; grade 1 (>2/3 of the whole small intestine), grade 2 (1/3∼2/3), grade 3 (<1/3), grade 4 (the duodenum). The SIC change was classified as follows; grade 1 and 2 or grade non-increase during follow-up was classified as "non-progressive", grade 3 and 4 or grade increase as "progressive". All SSc patients were evaluated the items as used for 2013 ACR/EULAR criteria. Results: The mean durations of follow-up period were 9.5±0.6 years. The number of SSc patients in each SIC grade at the initial evaluation and the end of follow-up were as follows; grade 1: initial vs end; 23 vs 24, grade 2: 20 vs 9, grade 3: 10 vs 16, grade 4: 2 vs 6. The SIC change "progressive" was 40.0% of SSc patients. Positive correlation between the esophageal diameters and the SIC grade was observed in SSc patients at the initial evaluation (r=0.61 p<0.01) and the end of follow-up (r=0.71 p<0.01). The esophageal diameters at the initial evaluation were significantly wider in SIC "progressive" group than in "non-progressive" group (non-progressive vs progressive; 21.8±6.5 vs 30.9±8.6 mm, p<0.0001). The frequencies of SSc patients with ACA-positive and sclerodactyly were higher but with puffy fingers were lower in SIC "progressive" group than in "non-progressive" group (non-progressive vs progressive; 24.2 vs 59.1%, p=0.009; 33.3 vs 63.6%, p=0.03; 72.7 vs 45.5%, p=0.03). The prevalence of pitting scar and Interstitial lung disease were tended to be higher in SIC "progressive" compared to SIC "non-progressive" group (non-progressive vs progressive; 15.6 vs 36.4%, p=0.07; 21.1 vs 45.5%, p=0.06). Conclusions: The present study demonstrated that the progression of small intestinal involvement was associated with esophageal dilatation at the initial evaluation during long-term follow-up of SSc patients. Our findings also suggested that ACA and skin thickening of the fingers were important factors of small intestinal involvement in SSc patients. The SIC may be a useful tool for the assessment of GI tract involvement in SSc patients during long-term follow-up. Disclosure of Interest: None declared